Formulation of geopolymer cement using mixture of slag and class f fly ash for oil well cementing - Kanesan, D. (Institute of Physics Publishing, 2017)
The increase in greenhouse gas emissions has been a factor for the increase in global temperature. Geopolymer cement has been intensively studied to replace conventional ordinary Portland cement, however the focus is limited to civil purposes under atmospheric conditions. This research focuses on the formulation of geopolymer cement to be used in oil well cementing application by taking account the effect of sodium hydroxide (NaoH) molarity, ratio of alkali binder and fly ash, amount of dispersant for oilwell operation under temperature ranging of 80°C and 90C° and pressure of 1000 and 3000psi. The formulated composition is tested for fluid loss where the standard has been from 60 to 80 ml. The cement slurry is cured in a 50mm x 50mm x 50mm mold for period of 24 hours. Four manipulating variables were set in formulating the cement slurry namely, the ratio between fly ash and slag to alkali binder, ratio of sodium hydroxide (NaoH) to sodium silicate, molarity of NaoH and amount of dispersant added. After running a set of 16 experiment, sample (12) was found to possess the best rheological properties and fluid loss according to API RP10B. It was found that as the curing temperature and pressure increase, the compressive strength of the formulated geopolymer cement also increased. © Published under licence by IOP Publishing Ltd.